Hemolytic events associated with intravenous immune globulin therapy: a qualitative analysis of 263 cases reported to four manufacturers between 2003 and 2012. Issue 2 (14th July 2015) - Berg, Roger; Shebl, Amgad; Kimber, Mary Clare; Abraham, Maria; Schreiber, George B.
<x xml:space="preserve">Abstract</x> BACKGROUND Objectives of this study were to identify possible patient and product risk factors for intravenous immune globulin (IVIG)‐associated hemolysis, a recognized side effect of IG therapy; analyze IVIG indications; and examine dose levels (g/kg body weight) and total IVIG dose administered. STUDY DESIGN AND METHODS Reports of IVIG‐associated hemolysis for 10 years (2003‐2012) for four participating IG manufacturers were identified using a uniform case definition (Standardized MedDRA Query "Hemolytic disorders, " Broad Scope, Version 16.0) and analyzed. RESULTS IVIG‐associated hemolysis appears to occur predominantly at dose levels exceeding 0.5 g/kg, with 72% of cases with known dose information having dose levels between 1 and 2.5, and can affect patients at any age, without a clear gender preference. No association was found between hemagglutinin exposure and development of hemolysis, nor between dose levels and odds of receiving a transfusion to treat hemolysis. Patients with blood group AB may be at higher risk of hemolysis than those with group A or B. CONCLUSION Data examined confirm that IVIG‐associated hemolysis predominantly occurs following infusion of high IVIG doses, and can affect patients at every age of both genders. While presence of hemagglutinins appears to play a major role in pathogenesis of hemolytic disorders, high hemagglutinin titers of IVIG products themselves seem to be of less relevance, indicating that the pathomechanism of IVIG‐associated hemolysis may be related to the presence, but not the absolute amount, of hemagglutinins. Patients with hemolysis had additional hemolytic risks such as multiple comorbidities and medication use. IG‐treated patients with multiple risks should be closely monitored for hemolysis.